Structural Performance of Reinforced Concrete Buildings Considering Variations in Column Cross-Section Orientation and Reinforcement Ratio - Muhammad Syarif; Iqbal Faruq (CV. Get Press Indonesia, 2026)
The seismic resilience of reinforced concrete (RC) buildings in high-risk earthquake regions is strongly influenced by the configuration of vertical structural elements. This study examines the combined effects of column cross-sectional orientation and longitudinal reinforcement ratios on the seismic performance of a 10-story RC building. Twelve structural models were developed using SAP2000 v24 and analyzed through nonlinear static pushover analysis. The models represented variations in column orientation (strong-axis and weak-axis) and reinforcement ratios ranging from 1% to 8%, based on the seismic characteristics of Padang, West Sumatra. Structural responses were evaluated using base shear capacity, displacement ductility, and interstory drift ratios, with validation conducted using the PEER Structural Performance Database. The findings indicate that column orientation has a greater impact on lateral stiffness and drift control than reinforcement quantity. Columns aligned along the strong axis with moderate reinforcement ratios between 2.5% and 3.5% demonstrated the best balance between strength and ductility, meeting the “Life Safety” performance requirements of SNI 1726:2019. In contrast, weak-axis columns with reinforcement ratios exceeding 4% showed limited improvement in stiffness and a higher tendency toward brittle shear failure. These results suggest that optimizing geometric configuration is more effective and economical than simply increasing reinforcement volume for improving seismic safety. The study concludes that strategic column axis alignment is a practical mitigation approach for earthquake-prone areas, while future studies should consider bi-directional dynamic loading for enhanced performance-based design evaluation.